Development of Highly Stable and Sensitive SAW UV Sensor Based on Ta2O5 Coated 1D ZnO/SnO2 Core–Shell Nanostructures - Kim, Sihyeok; Singh, Gurpreet; Jeong, Yoo Jae; Lee, Seongjun; Lee, Keekeun (Advanced Materials Technologies, 2023)
Despite extensive research on ultraviolet (UV) sensors based on core–shell heterostructures, most of them exhibit low sensitivities, slow response/recovery times, and unsatisfactory long-term stabilities, thereby limiting their use in real-time applications. To solve these problems, a highly sensitive and stable surface acoustic wave (SAW) UV sensor based on novel tantalum pentoxide (Ta2O5) coated 1D zinc oxide (ZnO)/tin dioxide (SnO2) core–shell nanostructures is introduced. The fabricated SAW-based UV sensor system, including sensor interface electronics, exhibits a high UV response, fast response/recovery time, and long-term stability. Prior to device fabrication, coupling of mode (COM) modeling is performed to calculate the optimal parameters for the SAW device. Photoluminescence and X-ray photoelectron spectroscopy measurements reveal that the Ta2O5 layer coating effectively suppresses the recombination of photogenerated carriers, leading to an increase in the carrier density and improvement in the UV sensing properties. The evaluated sensitivity and linearity of the proposed sensor are 120.36 ppm (mW cm−2)−1 and 0.988, respectively, in the range of 1–60 µW cm−2. The sensing mechanism of the proposed UV sensor is discussed in detail. Using COMSOL simulations and photo-corrosion experiments, it is found that the Ta2O5 coated ZnO/SnO2 core–shell heterostructure minimizes the effects of humidity and improves stability.
Keywords: Core shell; Core shell nano structures; Core-shell heterostructures; Core-shell nanostructures; Response/recovery time; Surface acoustic wave sensors; Surface acoustic waves; Tantalum pentoxide; Tantalum pentoxide (ta 2O 5); Ultraviolet sensors; core–shell; nanorods; passivation; surface acoustic wave sensors; tantalum pentoxide (Ta 2O 5)